Pengaruh Work-Life Balance, Keterampilan, dan Burnout terhadap Kinerja Dimediasi Budaya Kerja pada Karyawan Bank Rakyat Indonesia Cabang Semarang Pattimura (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of work-life balance, work skills, and burnout on performance mediated by work culture on employees of Bank Rakyat Indonesia Semarang Pattimura Branch Office. The study used a quantitative approach involving 100 employees. Data collection was carried out through questionnaires and analyzed using IBM SPSS Statistics 27 software. The results showed that work-life balance and burnout did not have a significant effect on employee performance. Work skills and work culture had a significant effect on employee performance. Work-life balance and work skills had a significant effect on work culture. Burnout had a significant negative effect on employee performance. Work-life balance and work skills had a significant effect on employee performance through work culture. However, burnout did not have a significant effect on employee performance through work culture. Based on these results, it is recommended that companies implement work flexibility policies, ongoing training programs, and mental health support to improve employee welfare, and conduct regular evaluations to develop an inclusive work culture in improving employee performance.